People's Republic of China : Staff Report for the 2012 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2012)
China's economy has been moderate in 2012, with a GDP growth of about 8 percent. Macroeconomic policies helped to maintain sustainable growth and continued to be adjusted in line with evolving conditions. The 2012 fiscal stance balanced the past stimulus with the growing economy. The authorities have taken necessary steps to accelerate the implementation of approved projects. Directors encouraged the authorities to accelerate the transformation of China's economy as conceived under the 12th Five-Year Plan.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet